Highly dielectric liquid crystal composition and device using same

The introduction of a liquid crystal composition with a bent structure liquid crystal compound addresses the need for high relative permittivity and spontaneous polarization, resulting in advanced devices with enhanced dielectric properties, including high capacity, light weight, and flexibility.

JP7662321B2Active Publication Date: 2025-04-15LG SCIENCEPARK JAPAN CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020167513
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-02
Publication Date
2025-04-15
Estimated Expiration
2040-10-02

AI Technical Summary

Technical Problem

There is a lack of liquid crystal compositions with high relative permittivity and spontaneous polarization values, which are essential for developing materials with superior dielectric properties for advanced devices.

Method used

A liquid crystal composition featuring a liquid crystal compound with a bent structure, exhibiting a high relative permittivity of 1×10^2 to 1×10^5 and spontaneous polarization values ranging from 100 to 2000 nC/cm^2, is proposed. This composition is designed to enhance the dielectric properties of devices.

Benefits of technology

The liquid crystal composition achieves high capacity, light weight, and flexibility in devices, significantly surpassing conventional dielectric materials in terms of dielectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662321000001
    Figure 0007662321000001
  • Figure 0007662321000002
    Figure 0007662321000002
  • Figure 0007662321000003
    Figure 0007662321000003
Patent Text Reader

Abstract

To provide a liquid crystal composition that has extremely high relative dielectric constants and spontaneous polarization values, and a device that includes the liquid crystal composition and achieves high capacity, light weight and flexibility.SOLUTION: A liquid crystal composition contains a liquid crystal compound having a bent structure and has a relative dielectric constant of 1×102 or more and a spontaneous polarization value of 100 (nC / cm2) or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a highly dielectric liquid crystal composition and a device using the same. [Background technology]

[0002] A dielectric is a material in which dielectric properties are superior to electrical conductivity, is non-conductive to DC voltage, and behaves as an insulator. Dielectrics are widely used in devices such as actuators, capacitors, vibration power generation elements, and dielectric memories.

[0003] 2. Description of the Related Art There have been many materials constituting dielectric materials, including ceramics, dielectric inorganic materials, dielectric polymer resins, dielectric liquid crystal compositions, and other dielectric liquid crystal compositions.

[0004] Ferroelectrics and antiferroelectrics are known as materials with high relative dielectric constants. A "ferroelectric" is a type of dielectric material in which dipoles are aligned and the direction of the dipoles can be reversed by an electric field. The property of dipole moments aligning spontaneously in this way is called ferroelectricity. In addition, "antiferroelectrics" have dipoles that alternately face in opposite directions along a certain direction, so the macroscopic spontaneous polarization is zero, but it is possible to change the free energy by applying a strong external electric field and forcibly cause a phase transition to ferroelectricity.

[0005] Representative examples of ferroelectrics or antiferroelectrics include inorganic ferroelectrics such as barium titanate and lead zirconate titanate, and organic ferroelectrics such as organic crystals and organic liquid crystals.

[0006] As the ferroelectric liquid crystal or antiferroelectric liquid crystal, for example, in Non-Patent Document 1 and Patent Document 1, a single-layer smectic phase (SmCA s ) and antiferroelectric bilayer phase (SmCA b It has been reported that a mixture of 16OAM5AMO16, which forms 16OAM5AMO16, exhibits ferroelectric liquid crystal properties.

[0007] Moreover, in Patent Document 2, 16OAM5AMO16 containing fluorine atoms exhibits a relative dielectric constant of about 100.

[0008] However, a liquid crystal composition having a high relative dielectric constant and a device using the same have not yet been developed and provided, and there is still a need to develop materials having high dielectric properties. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 5223141 [Patent Document 2] Patent application No. 2019-218479 [Non-patent literature]

[0010] [Non-Patent Document 1] “Dimeric compounds, Several Types of Bilayer Smectic Liquid Crystals with Ferroelectric and Antiferroelectric Properties in Binary Mixture of Dimeric Compounds” [Tatsuya Izumi et, al; J. Phys. Chem. B2006, 110, 47, 23911-23919] Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention proposes a liquid crystal composition having an extremely high relative dielectric constant and a device using the same that achieves high capacity, light weight and flexibility.

[0012] Another object of the present invention is to provide a liquid crystal composition which contains a liquid crystal compound having a bent structure and has an extremely high relative dielectric constant and spontaneous polarization value. [Means for solving the problem]

[0013] [One aspect of the present invention] According to the present invention, the following can be proposed as one aspect of the present invention. [1] Contains a liquid crystal compound with a bent structure and has a relative dielectric constant of 1×10 2 or more, and the spontaneous polarization value is 100 (nC / cm 2 ) or more. [2] The relative dielectric constant is 1×10 2 ~1×10 5 The spontaneous polarization value is 100 to 2000 (nC / cm 2 ) is a liquid crystal composition. [3] The liquid crystal composition according to [1] or [2], wherein the liquid crystal compound having a bent structure is a compound represented by the following formula (1), and the liquid crystal composition is composed of one or more liquid crystal compounds: [ka] (1) [During the ceremony, Ar 1 , Ar 2 , Ar 3 , and Ar 4are each independently a benzene, naphthalene, anthracene or biphenyl which may have a substituent, the substituent being a halogen atom, a cyano group, a nitro group or a carboxy group; L is an ester or an imine; R is both (left end and right end) or each independently an alkyl group having 4 to 20 carbon atoms, an alkenyl group having 4 to 20 carbon atoms, an alkynyl group having 4 to 20 carbon atoms, a methacryl group having 4 to 20 carbon atoms, an acrylic group having 4 to 20 carbon atoms, an alkyl group having 4 to 20 carbon atoms and an ether bond, an alkoxy group having 4 to 20 carbon atoms and an ether bond, a terminal 1,2-dimethoxyethane having an ether bond and an alkyl group having 4 to 20 carbon atoms, a terminal diethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal triethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal tetraethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, an alkenyl group having an ether bond and having 4 to 20 carbon atoms, an alkynyl group having an ether bond and having 4 to 20 carbon atoms, a methacryl group having an ether bond and having 4 to 20 carbon atoms, or an acrylic group having an ether bond and having 4 to 20 carbon atoms, wherein m and p are each independently an integer of 1 to 3, and n is any odd number selected from 1 to 9. [4] The Ar 1 , Ar 2 , Ar 3 and Ar 4 The liquid crystal composition according to [3], wherein is a benzene having a substituent. [5] The liquid crystal composition according to any one of [1] to [4], which has been subjected to a voltage treatment. [6] The voltage treatment is an AC voltage, and is 1 to 50 V. pp The liquid crystal composition according to [5], characterized in that the liquid crystal composition is prepared under the conditions of 1 / um. [7] The liquid crystal composition according to [5], wherein the voltage treatment is a direct current voltage and is carried out under conditions of 0.1 to 20 V / um. [8] A liquid crystal compound having a bent structure and a dielectric constant of 1×10 2or more, and the spontaneous polarization value is 100 (nC / cm 2 ) or more. [9] The relative dielectric constant is 1×10 2 ~1×10 5 The spontaneous polarization value is 100 to 2000 (nC / cm 2 ) .

[10] The device according to [8] or [9], wherein the liquid crystal compound having a bent structure is a compound represented by the following formula (2), and is composed of a single liquid crystal compound or a plurality of liquid crystal compounds: [ka] (2) [During the ceremony, Ar 1 , Ar 2 , Ar 3 , and Ar 4are each independently a benzene, naphthalene, anthracene or biphenyl which may have a substituent, the substituent being a halogen atom, a cyano group, a nitro group or a carboxy group; L is an ester or an imine; R is both (left end and right end) or each independently an alkyl group having 4 to 20 carbon atoms, an alkenyl group having 4 to 20 carbon atoms, an alkynyl group having 4 to 20 carbon atoms, a methacryl group having 4 to 20 carbon atoms, an acrylic group having 4 to 20 carbon atoms, an alkyl group having 4 to 20 carbon atoms and an ether bond, an alkoxy group having 4 to 20 carbon atoms and an ether bond, a terminal 1,2-dimethoxyethane having an ether bond and an alkyl group having 4 to 20 carbon atoms, a terminal diethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal triethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal tetraethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, an alkenyl group having an ether bond and having 4 to 20 carbon atoms, an alkynyl group having an ether bond and having 4 to 20 carbon atoms, a methacryl group having an ether bond and having 4 to 20 carbon atoms, or an acrylic group having an ether bond and having 4 to 20 carbon atoms, wherein m and p are each independently an integer of 1 to 3, and n is any odd number selected from 1 to 9.

[11] The Ar 1 , Ar 2 , Ar 3 and Ar 4 The device according to

[10] , wherein is benzene having a substituent.

[12] The device according to any one of [8] to

[11] , comprising at least two electrodes and the liquid crystal composition sandwiched between the electrodes.

[13] The device according to

[12] , wherein the device is an actuator, a capacitor, a vibration power generation element, or a dielectric memory.

[14] The device according to any one of [8] to

[13] , which has been subjected to a voltage treatment.

[15] The voltage treatment is an AC voltage, and the voltage is 1 to 50 V. ppThe device described in

[14] is characterized in that the measurement is performed under conditions of 0.1 μg / um.

[16] The device according to

[14] , wherein the voltage treatment is a direct current voltage and is carried out under conditions of 0.1 to 20 V / um. Effect of the Invention

[0014] According to the present invention, the relative dielectric constant is 1×10 2 or more, and the spontaneous polarization value is 100 (nC / cm 2 It is possible to realize a liquid crystal composition containing a liquid crystal compound having a bent structure with a high relative dielectric constant and spontaneous polarization value of 100 kJ / mol / L or more. Furthermore, a device including the liquid crystal composition according to the present invention can realize a high capacity, light weight, and flexibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Liquid crystal compound] The liquid crystal compound having a bent structure used in the present invention is preferably a compound represented by the following formula (1). This liquid crystal compound exhibits a high relative dielectric constant, and can exhibit excellent performance as a dielectric. In the present invention, the liquid crystal compound is preferably a dimer.

[0016] [ka] (1) [During the ceremony, Ar 1 , Ar 2 , Ar 3 , and Ar 4are each independently a benzene, naphthalene, anthracene or biphenyl which may have a substituent, the substituent being a halogen atom, a cyano group, a nitro group or a carboxy group; L is an ester or an imine; R is both (left end and right end) or each independently an alkyl group having 4 to 20 carbon atoms, an alkenyl group having 4 to 20 carbon atoms, an alkynyl group having 4 to 20 carbon atoms, a methacryl group having 4 to 20 carbon atoms, an acrylic group having 4 to 20 carbon atoms, an alkyl group having 4 to 20 carbon atoms and an ether bond, an alkoxy group having 4 to 20 carbon atoms and an ether bond, a terminal 1,2-dimethoxyethane having an ether bond and an alkyl group having 4 to 20 carbon atoms, a terminal diethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal triethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, a terminal tetraethylene glycol dimethyl ether having an ether bond and an alkyl having 4 to 20 carbon atoms, an alkenyl group having an ether bond and having 4 to 20 carbon atoms, an alkynyl group having an ether bond and having 4 to 20 carbon atoms, a methacryl group having an ether bond and having 4 to 20 carbon atoms, or an acrylic group having an ether bond and having 4 to 20 carbon atoms, wherein m and p are each independently an integer of 1 to 3, and n is any odd number selected from 1 to 9.

[0017] [Liquid Crystal Composition] The liquid crystal composition of the present invention has a relative dielectric constant of 1×10 2 or more, and the spontaneous polarization value is 100 (nC / cm 2 ) or more, and preferably contains a liquid crystal compound having the above-mentioned bent structure. The relative dielectric constant and spontaneous polarization value will be described later.

[0018] (Dielectric constant) The liquid crystal compound used in the present invention has a 1×10 1 ~1×10 5 On the order of 1×10 2 More preferably, 1×10 3More than 1×10, most preferably 4 That is, due to such properties, the liquid crystal composition of the present invention has a high relative dielectric constant of 1×10 2 The relative dielectric constant can be measured at a frequency of about 1 Hz to 1 kHz, preferably about 10 Hz to 100 Hz, and more specifically at 10 Hz.

[0019] Generally, the relative dielectric constant can be measured under the conditions of JIS C2138:2007, but it can also be measured using a commercially available impedance analyzer. The impedance analyzer used is FRA51615 (manufactured by NF Corporation), and the measurement can be performed under the conditions of a frequency (variable) of 10Hz to 15MHz and a measurement temperature of 20°C to 200°C. As an example, the sample to be measured can be prepared by laminating a dielectric material with a thickness of about 10nm to 1μm on a 2cm square indium tin oxide, and forming a circular electrode (e.g., a metal such as copper, chromium, aluminum, or gold) with a diameter of 1mm to 10mm on the dielectric material by vapor deposition.

[0020] (Spontaneous polarization value) Generally, ferroelectrics change their crystal form at a certain temperature called the Curie point; above the Curie point they lose their spontaneous polarization and become paraelectric, and below the Curie point they develop spontaneous polarization and become ferroelectric.

[0021] At or above the Curie point, the relative dielectric constant (ε) satisfies the following relationship, known as the Curie Weiss law. ε=C / (T-Tr) (In the formula, C is the Curie constant, Tr is the Curie temperature (°C), and T is the measurement temperature (°C).)

[0022] Generally, a large spontaneous polarization value indicates a large charge density that can be accumulated on the surface of a material, which is advantageous not only for miniaturizing nonvolatile memory cells but also for improving the performance of dielectric, pyroelectric, and piezoelectric properties. In addition, the above-mentioned relative dielectric constant and spontaneous polarization value are independent variables only for liquid crystal compounds having a bent structure. This is because the liquid crystal compounds having a bent structure of the present application form a specific orientation structure such as a smectic phase, and the relative dielectric constant increases significantly with an increase in the dipole moment.

[0023] [Method for producing liquid crystal compound] (Production Example of Liquid Crystal Compounds (1) and (2)) The liquid crystal compounds represented by (1) and (2) above can be produced by a conventional production method, specifically, by producing a plurality of intermediates and combining these intermediates to obtain the liquid crystal compound.

[0024] As the raw material, a compound capable of forming the basic skeleton of the liquid crystal compound represented by (1) or (2) above is prepared. For example, R may be alkyl or alkoxy (which may be substituted with halogen) having 4 to 20 carbon atoms. 1 , Ar 2 , Ar 3 , and Ar 4 The alkyl group may be benzene, naphthalene, anthracene, or biphenyl having a substituent. O(CH 2 ) n O may be an alkyl diol.

[0025] A reactor equipped with a stirrer, a condenser, a heating device, a gas inlet tube and a temperature control device is prepared, and raw materials, reagents, solvents, gases, etc. are appropriately introduced, and the temperature, pressure, introduction rate of raw materials, etc. in the reactor are appropriately adjusted to obtain the liquid crystal compounds represented by (1) and (2) above. The structure of the obtained intermediate is analyzed by NMR.

[0026] [Method of crosslinking (fixing) liquid crystal compounds] The liquid crystal compounds represented by (1) and (2) can be crosslinked (fixed) to fix the liquid crystal alignment state of the film formed. As a method for this, the liquid crystal compounds represented by (1) and (2) can be crosslinked by exposure to light having a wavelength of 13.5 to 436 nm and heating at 40 to 200° C. In addition, in order to promote crosslinking, a crosslinking agent and a catalyst (photoacid generator, photobase generator, photoradical generator, thermal acid generator, thermal base generator, and thermal radical generator) can be added to the liquid crystal compounds represented by (1) and (2) to perform crosslinking.

[0027] 〔device〕 The present invention proposes a device comprising the liquid crystal composition of the present invention.

[0028] In recent years, dielectrics mounted on electrochemical elements such as actuators and capacitors are required to have high capacitance as one of the performance improvements of electrochemical elements. For example, in a capacitor, the "capacitance" is defined by the following formula, and in order to achieve "high capacitance", a high relative dielectric constant is required in the following formula. C=εε 0 S / d [In the above formula, C is the capacitance, ε is the relative dielectric constant of the dielectric, and ε 0 is the dielectric constant of a vacuum, S is the electrode area, and d is the distance between the electrodes.

[0029] Since the device according to the present invention comprises the liquid crystal composition of the present invention, which exhibits a higher dielectric constant than conventional dielectric materials, it is possible to realize a high dielectric constant, and as a result, it is possible to realize a high capacity for a device incorporating the liquid crystal composition of the present invention.

[0030] The device may have a desired shape, such as a film, sheet, plate, fiber, rod, cube, rectangular parallelepiped, sphere, rugby ball, composite shape, or complex shape, depending on the intended use. When the device according to the present invention has a planar shape such as a film, sheet, or plate, its thickness can be freely determined depending on the desired mode of use.

[0031] The present invention proposes a device comprising the liquid crystal composition according to the present invention. The device of the present invention may preferably have a configuration comprising at least two electrodes and the liquid crystal composition according to the present invention between the electrodes. Examples of such devices include actuators, capacitors, vibration power generation elements, (ferro)dielectric memories, filters in communication devices, antennas, key devices in mobile phones, and the like. The liquid crystal compound (or dielectric) according to the present invention particularly contributes greatly to the realization of actuators, capacitors, vibration power generation elements, dielectric memories, and the like that have a high relative dielectric constant and combine high properties with light weight.

[0032] In recent years, devices such as actuators, capacitors, and vibration power generation elements have also been attracting attention as wearable devices. In addition to flexibility, wearable devices must also be capable of being driven at a low voltage from the standpoint of safety.

[0033] The device according to the present invention comprises the liquid crystal composition of the present invention, which exhibits higher flexibility (flexibility) than conventional dielectric materials, and therefore it is possible to not only improve the characteristics of each of the above-mentioned devices, but also to realize flexibility and low-voltage operation.

[0034] (Actuator) An actuator, particularly a dielectric actuator, comprising the liquid crystal composition according to the present invention can be proposed. A dielectric actuator has a structure in which an elastomer is sandwiched between two electrodes, and in an electric field, a positive charge is stored in one electrode and a negative charge is stored in the opposite electrode. As a result, a Coulomb force is generated between the electrodes, and this Coulomb force causes the elastomer to be crushed by the electrodes, thereby functioning as an actuator. The force generated by a dielectric actuator is defined by the following formula, and can be controlled by changing the relative dielectric constant, the distance between the electrodes, the electrode area, and the voltage. F = εε 0 S.V. 2 / 2d 2 [In the above formula, F is the generated force, ε is the relative dielectric constant of the dielectric (elastomer), and ε 0is the dielectric constant of a vacuum, S is the electrode area, V is the applied voltage, and d is the distance between the electrodes. In order to realize high performance as a dielectric actuator, a high generated force is necessary, and the dielectric constant in the above formula must be high.

[0035] The strain of an elastomer is defined by the following formula: σ=Fd / E (In the above formula, σ is the strain, F is the generated force, d is the distance between the electrodes, and E is the Young's modulus.) Furthermore, in order to realize high characteristics as a dielectric actuator, high generated force and large strain are necessary, and from the above formula, the performance of the elastomer needs to have a small Young's modulus (high flexibility).

[0036] One possible method for generating a large force is to increase the voltage, but from the perspective of safety, it is desirable for a dielectric actuator for a wearable device to be driven by a low voltage.

[0037] A (dielectric) actuator comprising the liquid crystal composition according to the present invention can realize a high generating force and a large strain, and can also realize flexibility and low-voltage drivability, as compared with conventional (dielectric) actuator materials. The dielectric actuator may have a multi-layer laminate of liquid crystal composition and electrodes as its element. In the dielectric actuator of the present invention, the layer thickness of the liquid crystal compound is about 0.1 to 500 μm, and a generating force (F) of 10 to 5000 N can be realized.

[0038] The material of the electrodes (anode, cathode) may be a normal conductive material, for example, carbon materials such as carbon nanofibers and carbon black, metal colloids such as colloidal silver, charge transfer complexes such as tetrathiafulvalene / tetracyanoquinodimethane, conductive polymers such as polypyrrole, etc., and preferably a material having elasticity that follows the expansion and contraction of the dielectric material used. Examples of such electrode members include composite materials in which a conductive filler is dispersed in resins such as acrylic, silicon, urethane, and styrene elastomer materials, and highly viscous materials such as silicon grease.

[0039] The dielectric actuator of the present invention can be produced by a method including spraying the liquid crystal composition of the present invention onto an electrode material; laminating an electrode material and a dielectric; impregnating or dispersing a dielectric into an electrode material; or coating or printing a dielectric onto an electrode material.

[0040] The dielectric actuator according to the present invention can operate in various environments (gas, liquid, solid), as well as in equipment, living organisms, etc. The dielectric actuator according to the present invention enables easy response and rapid response in the movable area (particularly the joints) of a robot or the like in which it is mounted, or can be used to assist the movement of animals (including humans) by attaching it to a living organism (e.g., human skin). The present invention can propose a dielectric actuator for motion assistance.

[0041] For example, the liquid crystal composition according to the present invention has a high relative dielectric constant and therefore functions as a dielectric elastomer. That is, when a voltage is applied between the electrodes, a Coulomb force is generated between the electrodes, and this Coulomb force causes the dielectric elastomer to be crushed by the electrodes. When the voltage application is stopped, the dielectric returns to its original state due to its elasticity. Therefore, contraction-expansion can be reversibly controlled by turning the voltage ON-OFF, and it can be used as a dielectric actuator.

[0042] In particular, in the present invention, the dielectric actuator according to the present invention is used as a driving system in artificial muscles, robots, assisting devices, etc., and can meet the demand for high generating force.

[0043] (Capacitor) A capacitor comprising the liquid crystal composition according to the present invention basically comprises a high dielectric constant liquid crystal compound between two electrodes, and may comprise a multi-layer laminate of liquid crystal composition and electrodes. Since the capacitor according to the present invention comprises a high dielectric constant liquid crystal composition, the layer thickness of the liquid crystal composition is about 0.1 to 500 μm, and the capacitance (C) can be 1 pF to 10,000 μF.

[0044] The capacitor according to the present invention may be constructed in a conventional manner, except that the liquid crystal composition according to the present invention is used. Therefore, the materials of the two electrode plates (anode, cathode) may be constructed as conventional materials, and the above-mentioned manufacturing example may be the same as that explained in the section on [Actuator]. The capacitor according to the present invention can also be used as an electronic circuit component.

[0045] (Vibration power generation element) A vibration power generation element comprising the liquid crystal composition of the present invention generates electricity based on the opposite principle to that of the actuator described above, and converts almost unused energy, such as the movements of animals and plants and the swaying of artificial objects, into electricity (power generation).

[0046] The vibration power generating element according to the present invention basically comprises the liquid crystal composition according to the present invention between at least two electrodes. Therefore, the configuration may be the same as that explained in the above [Actuator] section. Since the vibration power generating element according to the present invention comprises the high dielectric constant liquid crystal composition according to the present invention, the layer thickness of the liquid crystal composition according to the present invention is about 0.1 μm to 1 cm, and the power (E) per one expansion and contraction can be realized to be 0.1 mW to 10 W.

[0047] (Ferroelectric Memory) The present invention can propose a (ferro)electric memory comprising the liquid crystal composition or derivative according to the present invention. The "(ferro)electric memory" is a non-volatile memory in which positive and negative remanent polarization (spontaneous polarization) caused by the hysteresis of a ferroelectric corresponds to digital data, and is known as Ferroelectric Random Access Memory (FeRAM).

[0048] The dielectric memory is composed of a semiconductor layer, an insulating layer, an antiferroelectric, a ferroelectric, an electrode, and a source region and a drain region formed in the semiconductor layer. In the present invention, the liquid crystal composition or the dielectric according to the present invention is used as the antiferroelectric or the ferroelectric (preferably).

[0049] A (ferro)dielectric memory using the liquid crystal composition according to the present invention can be realized with a dielectric layer thickness of about 0.1 to 500 μm. EXAMPLES

[0050] The present invention will be described with reference to the following examples, but the scope of the present invention is not limited to these examples. In addition, various aspects of the present invention disclosed in this specification can be easily implemented by those skilled in the art from these examples. [Synthesis of Liquid Crystal Compounds]

[0051] (liquid crystal compound 1) The liquid crystal compound 1 can be synthesized according to Non-Patent Document 1.

[0052] (liquid crystal compound 2) The liquid crystal compound 2 can be synthesized according to Non-Patent Document 1.

[0053] (liquid crystal compound 3) The liquid crystal compound 3 can be synthesized according to Patent Document 2.

[0054] [Preparation of Liquid Crystal Composition and Electrochemical Device] (Liquid crystal compound 1 (35mol%) + liquid crystal compound 2 (65mol%)) Liquid crystal compound 1 (1.00 g, 1.00 mmol) and liquid crystal compound 2 (1.23 g, 1.86 mmol) were mixed, and chloroform (Kanto Chemical, 109.34 g) was added. After complete dissolution, the solution was kept at 50° C. and the chloroform was evaporated to obtain liquid crystal compound 1 (35 mol%) + liquid crystal compound 2 (65 mol%). The obtained liquid crystal composition was melted by heating to 120° C., and placed in a cell (EHC, electrode area: 1 cm) sandwiched between glass substrates with ITO (electrodes). 2 Electrochemical elements were fabricated by injecting the solution into the electrodes (electrode distance: 3, 10, 25, 50 μm).

[0055] (Liquid crystal compound 1 (70mol%) + liquid crystal compound 2 (30mol%)) Liquid crystal compound 1 (1.00 g, 1.00 mmol) and liquid crystal compound 2 (0.28 g, 0.43 mmol) were mixed, chloroform (62.92 g) was added, and after complete dissolution, the solution was kept at 50°C and the chloroform was evaporated to obtain liquid crystal compound 1 (70 mol%) + liquid crystal compound 2 (30 mol%). The obtained liquid crystal composition was melted by heating to 120°C and sandwiched between glass substrates with ITO (electrodes) to form a cell (electrode area: 1 cm). 2 An electrochemical element was fabricated by injecting the solution into a semiconductor substrate (electrode distance: 3 μm).

[0056] (liquid crystal compound 3) Liquid crystal compound 3 was melted by heating to 120°C and sandwiched between glass substrates with ITO (electrodes) to form a cell (electrode area: 1 cm 2 An electrochemical element was fabricated by injecting the solution into a semiconductor substrate (electrode distance: 3 μm).

[0057] (Liquid crystal compound 3 (60mol%) + liquid crystal compound 2 (40mol%)) Liquid crystal compound 3 (1.00 g, 0.97 mmol) and liquid crystal compound 2 (0.43 g, 0.64 mmol) were mixed, chloroform (69.91 g) was added, and after complete dissolution, the solution was kept at 50°C and the chloroform was evaporated to obtain liquid crystal compound 3 (60 mol%) + liquid crystal compound 2 (40 mol%). The obtained liquid crystal composition was melted by heating to 120°C and placed in a cell (electrode area: 1 cm) sandwiched between glass substrates with ITO (electrodes). 2 An electrochemical element was fabricated by injecting the solution into a semiconductor substrate (electrode distance: 3 μm).

[0058] Example 1 A liquid crystal cell (electrode area: 1 cm) containing liquid crystal compound 1 (35 mol%) and liquid crystal compound 2 (65 mol%) 2 , electrode distance: 3um) at a liquid crystal phase temperature of 104℃, and an impedance analyzer (FRA51615, manufactured by NF Corporation) was used to process the AC voltage at 10V pp / um. Then, an impedance analyzer was used to measure the voltage at 1 V pp The relative dielectric constant (dielectric strength) was measured by sweeping the frequency from 10 Hz to 15 MHz and found to be 1640. In addition, at a liquid crystal phase temperature of 104°C, a 10V AC voltage with a triangular wave was applied to the liquid crystal cell from a function generator (WF1945B, NF Circuit Design Block). pp A voltage of 1000 nC / cm was applied to the sample, and the potential on the resistor, which was an IV converter, was measured using an oscilloscope (TDS2014, Tektronix). The spontaneous polarization was calculated from the integral value of the obtained waveform, and was found to be 786 nC / cm 2 The capacitance was 786 nC. The evaluation results are shown in Table 1 below.

[0059] Example 8 Liquid crystal cell (electrode area: 1 cm) containing liquid crystal compound 1 (70 mol%) and liquid crystal compound 2 (30 mol%) 2 , electrode distance: 3um) at a liquid crystal phase temperature of 116℃, and an AC voltage treatment of 10V using an impedance analyzer. pp / um. Then, an impedance analyzer was used to measure the voltage at 1 V pp The relative dielectric constant (dielectric strength) was measured at a DC voltage of 1 V / um and a frequency sweep of 10 Hz to 15 MHz, and was found to be 620.

[0060] (Examples 2 to 7, 9, and 11, and Comparative Example 6) The experiment was carried out in the same manner as in Example 1, and the results and conditions of the experiment are shown in Table 1.

[0061] (Examples 10 and 12) The experiment was carried out in the same manner as in Example 8, and the results and conditions of the experiment are shown in Table 1.

[0062] Comparative Example 1 Dielectric measurement electrode (electrode area: 1 cm 2 An electrochemical element was prepared by sandwiching polyvinylidene fluoride rubber (manufactured by Kayo Bussan Co., Ltd., electrode distance (film thickness): 500 um) between the electrodes. The AC voltage treatment was performed at 5 V at 25 °C using an impedance analyzer. pp / um. Then, an impedance analyzer was used to measure the voltage at 1 V pp The relative dielectric constant (dielectric strength) was measured by sweeping the frequency from 10 Hz to 15 MHz, and was found to be 13. The experimental results and conditions are shown in Table 1.

[0063] Comparative Example 2 Dielectric measurement electrode (electrode area: 1 cm 2 An electrochemical element was prepared by sandwiching polyvinylidene fluoride rubber (manufactured by Kayo Bussan Co., Ltd., electrode distance (film thickness): 500 um) between the electrodes. The AC voltage treatment was performed at 5 V at 25 °C using an impedance analyzer. pp / um. Then, an impedance analyzer was used to measure the voltage at 1 V pp The relative dielectric constant (dielectric strength) was measured at a DC voltage of 1 V / um and a frequency sweep of 10 Hz to 15 MHz, and was found to be 13. The experimental results and conditions are shown in Table 1. (Comparative Examples 3 to 5) An experiment was carried out in the same manner as in Comparative Example 1, and the experimental results and conditions are shown in Table 1. [Table 1]

[0064] In Table 1, Liquid Crystals 1 to 3 are liquid crystal compounds having the following structures:

[0065] LCD 1: [ka]

[0066] LCD 2: [ka]

[0067] LCD 3: [ka] [Industrial Applicability]

[0068] The present invention can provide a liquid crystal composition having an extremely high relative dielectric constant and a device using the same that achieves high capacity, light weight, and flexibility. The present invention can also provide a liquid crystal composition containing a liquid crystal compound having a bent structure and having an extremely high relative dielectric constant and spontaneous polarization value. For the above reasons, the present invention is extremely useful industrially.

Claims

1. A liquid crystal composition comprising: Contains a liquid crystal compound having a bent structure and has a relative dielectric constant of 1×10 2 or more, and the spontaneous polarization value is 100 (nC / cm 2 ) and The liquid crystal compound is a compound represented by the following formula (1): 【Chemistry 1】 [In the formula, Ar 1 , Ar 2 , Ar 3 , and Ar 4 are each independently a benzene which may have a halogen atom as a substituent, L is an imine or an ester, R is both (left end and right end) or each independently an alkyl group having 4 to 20 carbon atoms and an ether bond, m and p are each independently an integer of 1 to 3, and n is 5.] the liquid crystal composition is composed of one or more of the liquid crystal compounds, A liquid crystal composition, wherein the liquid crystal compound forms a smectic phase alignment structure.

2. The dielectric constant is 1×10 2 ~1×10 5 and the spontaneous polarization value is 100 to 2000 (nC / cm 2 2. The liquid crystal composition according to claim 1, wherein

3. The liquid crystal composition according to claim 1 or 2, which has been subjected to a voltage treatment.

4. The voltage treatment is an AC voltage of 1 to 50 V pp The liquid crystal composition according to claim 3, characterized in that the liquid crystal composition is subjected to the reaction under the conditions of:

5. 4. The liquid crystal composition according to claim 3, wherein the voltage treatment is a direct current voltage and is carried out under conditions of 0.1 to 20 V / um.

6. A device comprising a liquid crystal composition, Contains a liquid crystal compound having a bent structure and has a relative dielectric constant of 1×10 2 or more, and the spontaneous polarization value is 100 (nC / cm 2 ) and The liquid crystal compound is a compound represented by the following formula (1): 【Chemistry 1】 [In the formula, Ar 1 , Ar 2 , Ar 3 , and Ar 4 are each independently a benzene which may have a halogen atom as a substituent, L is an imine or an ester, R is both (left end and right end) or each independently an alkyl group having 4 to 20 carbon atoms and an ether bond, m and p are each independently an integer of 1 to 3, and n is 5.] the liquid crystal composition is composed of one or more of the liquid crystal compounds, A device comprising a liquid crystal composition, wherein the liquid crystal compound has a smectic phase orientation structure.

7. The dielectric constant is 1×10 2 ~1×10 5 and the spontaneous polarization value is 100 to 2000 (nC / cm 2 7. The device of claim 6, comprising a liquid crystal composition comprising:

8. 8. The device according to claim 6, comprising at least two electrodes and the liquid crystal composition sandwiched between the electrodes.

9. The device according to claim 8 , wherein the device is an actuator, a capacitor, a vibration power generating element, or a dielectric memory.

10. 8. The device of claim 6 or 7, which has been subjected to a voltage treatment.

11. The voltage treatment is an AC voltage of 1 to 50 V pp The device according to claim 10, characterized in that the device is subjected to the above-mentioned conditions.

12. The device according to claim 10, characterized in that the voltage treatment is a direct current voltage and is carried out under conditions of 0.1 to 20 V / um.

Citation Information

Patent Citations

  • Finishing method by the double coating with powder coating

    JP1977023141A

  • Liquid crystal display device

    JP1998161128A

  • Liquid crystal display device and liquid crystal molecules

    JP1998161145A

  • Liquid crystal cell device and method of manufacturing liquid crystal cell device

    JP2003066493A

  • Liquid crystalline compound and liquid crystal display

    JP2010047672A